2006
DOI: 10.1016/j.amjhyper.2005.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Education on Blood Pressure Control in Elderly PersonsA Randomized Controlled Trial

Abstract: Based on these study results, the self-management education model was significantly more effective than the compliance-based model in BP control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
2
41
0
7
Order By: Relevance
“…Health education is an essential tool in the prevention and control of chronic non-communicable diseases [17–19]. Monitoring the evolution of some risk factors for CVD in individuals with health-related degrees could, theoretically, determine the real impact of health education as a measure of health promotion because this population has formal training in healthcare and therefore has deeper knowledge of the risks and effects of risk factors for CVD and the risk behaviors associated with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Health education is an essential tool in the prevention and control of chronic non-communicable diseases [17–19]. Monitoring the evolution of some risk factors for CVD in individuals with health-related degrees could, theoretically, determine the real impact of health education as a measure of health promotion because this population has formal training in healthcare and therefore has deeper knowledge of the risks and effects of risk factors for CVD and the risk behaviors associated with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also revealed that the power of home blood pressure measurement to predict target-organ damage is comparable to that of the ''gold standard,'' that is, ambulatory monitoring [24]. Self-monitoring is also discussed as an act of ''patient empowerment'' that is correlated with better outcomes [25,26]. Although self-measurement of blood pressure seems to be valid and to have beneficial effects, the reliability of self-reported blood pressure measurements may be a separate matter for concern.…”
Section: Criterion Validitymentioning
confidence: 96%
“…Most patients in the intervention and the control group were illiterate. (Both groups 47.1) In Figer's [22] study, most patients had low education. In Abbas Heidari's study, 39.5% of patients were illiterate.…”
Section: Discussionmentioning
confidence: 99%